2021
DOI: 10.7717/peerj.12244
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary placement and new records of an overlooked Amazonian tree, Christiana mennegae (Malvaceae)

Abstract: Christiana mennegae is a phylogenetically enigmatic taxon and represents a case in point of a species whose presence escaped the radar of the Amazon lists and the Brazilian Flora project. Here we expand its distribution by adding new records from Peru and overlooked ones from Brazil. To investigate its phylogenetic placement in the Brownlowioideae, part of the rbcL gene of the plastid and the intergenic ITS2 region were sequenced. Macro- and micro-morphological investigation of features of C. mennegae using SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…4 b, c, d, e, f, g), while based on concatenation of atp B, mat K and ndh F or atp B, trn K- mat K, ndh F, rbc L and ITS showed that Dombeyoideae was the first divergent (Fig. 4 h) [ 37 , 86 ]. The topologies between Tilioideae, Brownlowioideae, and Sterculioideae have been largely incongruent and remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…4 b, c, d, e, f, g), while based on concatenation of atp B, mat K and ndh F or atp B, trn K- mat K, ndh F, rbc L and ITS showed that Dombeyoideae was the first divergent (Fig. 4 h) [ 37 , 86 ]. The topologies between Tilioideae, Brownlowioideae, and Sterculioideae have been largely incongruent and remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the effective implementation of conservation, especially for endemic species with unique habitats [46], further research needs to be conducted to determine the genetic diversity of all populations, and inbreeding and genetic diversity levels [22,46] could be used to determine protection priorities, especially at the landscape level. Information on the population size, phenological patterns, morphological variations [47,48], and population genetic diversity [49] in natural habitats, including the populations in the northern and central part of Sulawesi, will determine the actions that should be taken concerning conservation in natural habitats (in-situ). This conservation should involve the indigenous knowledge of "Eluren Eng Kayobaan" (keeping and maintaining the Earth) [50] to encourage the planting of Wasian trees on community lands.…”
Section: Discussionmentioning
confidence: 99%